2022
DOI: 10.1001/jama.2022.21680
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mindfulness Training and Exercise on Cognitive Function in Older Adults

Abstract: ImportanceEpisodic memory and executive function are essential aspects of cognitive functioning that decline with aging. This decline may be ameliorable with lifestyle interventions.ObjectiveTo determine whether mindfulness-based stress reduction (MBSR), exercise, or a combination of both improve cognitive function in older adults.Design, Setting, and ParticipantsThis 2 × 2 factorial randomized clinical trial was conducted at 2 US sites (Washington University in St Louis and University of California, San Diego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 42 publications
4
45
0
1
Order By: Relevance
“…On the other hand, in our study, one of the explanations of the effectiveness of MBI training for the emotional regulation of attention may be the effect of reducing mental distractions by focusing on the mental and emotional contents of the present moment with a non-judgmental attitude. Furthermore, MBI emotional regulation involves a greater ability to maintain a state of attention (alertness) to the activity and improved performance in executive control and memory enhancement tasks, as both behavioral and neuroimaging studies have determined [ 18 , 20 , 21 , 22 , 23 ]. This emotional regulation is effective in reducing stress and problematic psycho-emotional states (e.g., sleep disorders, stress, depression) [ 28 ], known as risk factors for the onset and worsening of cognitive performance, mental health, and well-being of the aging population and are associated with an increased risk and worsening of Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in our study, one of the explanations of the effectiveness of MBI training for the emotional regulation of attention may be the effect of reducing mental distractions by focusing on the mental and emotional contents of the present moment with a non-judgmental attitude. Furthermore, MBI emotional regulation involves a greater ability to maintain a state of attention (alertness) to the activity and improved performance in executive control and memory enhancement tasks, as both behavioral and neuroimaging studies have determined [ 18 , 20 , 21 , 22 , 23 ]. This emotional regulation is effective in reducing stress and problematic psycho-emotional states (e.g., sleep disorders, stress, depression) [ 28 ], known as risk factors for the onset and worsening of cognitive performance, mental health, and well-being of the aging population and are associated with an increased risk and worsening of Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Promising interventions are mindfulness-based interventions (MBIs), which, as opposed to mere cognitive training, improve moment-to-moment attention control while simultaneously [ 20 , 21 , 22 , 23 , 24 , 25 ] reducing distractions due to internal and external interruptions. The other benefits of these meditation or mindfulness practices are a reduction in stress and an improvement in mood, quality of life, and socio-emotional and cognitive balance in general [ 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating reports indicate that elevated levels of insulin-like growth factor, brain-derived neurotrophic factor (BDNF), and other neurotrophic factors are involved in the improvement of cognitive function through exercise [ 7 , 8 , 9 , 10 , 11 ]. Meanwhile, an 18-month exercise intervention did not show any cognitive improvement in healthy older adults [ 12 ]. Comparing the effects of physical exercise in originally active and inactive older adults, the intervention was not effective on cognitive performance in both groups [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Reply We thank Drs Salmoirago-Blotcher and Cohen for their interest in the MEDEX study, which showed that mindfulness training and/or exercise did not improve cognitive function in older adults with subjective cognitive concerns. However, we disagree with their concern that the negative findings “can be explained by…methodological limitations.”…”
mentioning
confidence: 98%